2020
DOI: 10.1542/peds.2020-1429
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines on Deferred Cord Clamping and Cord Milking: A Systematic Review

Abstract: CONTEXT: Deferred cord clamping (DCC) saves lives. It reduces extremely preterm infants' mortality by 30%, yet a minority of eligible infants receive it. This may in part be due to lack of awareness or confidence in evidence, or conflicting or vague guidelines.OBJECTIVE: To systematically review clinical practice guidelines and other statements on DCC and cord milking.DATA SOURCES: Ten academic and guideline databases were searched.STUDY SELECTION: Clinical practice guidelines and other statements (position st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 52 publications
0
11
0
2
Order By: Relevance
“…The implementation of delayed CC practice varies between countries, and international and national guidelines differ depending on mode of delivery and complications at birth [ 4 ]. Hence, more studies of specific clinical situations and different implementation settings are needed.…”
Section: Introductionmentioning
confidence: 99%
“…The implementation of delayed CC practice varies between countries, and international and national guidelines differ depending on mode of delivery and complications at birth [ 4 ]. Hence, more studies of specific clinical situations and different implementation settings are needed.…”
Section: Introductionmentioning
confidence: 99%
“…During the last decade, research has demonstrated the benefits for the neonate of delaying CC [18][19][20] , and this finding has led to a change in the strategies for timing of umbilical CC and cutting, in Sweden and several other countries as well 21 . Several barriers for implementation exist, but a multidisciplinary approach is needed for practice to be adopted 22 .…”
Section: Discussionmentioning
confidence: 99%
“…A statewide California quality improvement (QI) collaborative reported inter-hospital variation in DCC from 0 to 74% and only 29% of newborns overall receiving DCC in 2016 [3]. A proliferation of clinical practice guidelines, which differ in their details and sometimes fail to reflect the most recent evidence, may actually add to uncertainty and reluctance to change existing practice [4].…”
Section: Introductionmentioning
confidence: 99%